Rancang Bangun Pakan Ikan Otomatis dan Kontroling Suhu Serta Monitoring pH Air Berbasis IoT - Robiyanto, Robi; Subakti, Tresna; Raswa; Al Hilmi, Muhammad Anis (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2024)
This research proposes the design of an automatic fish feeding system equipped with temperature control and water pH monitoring based on the Internet of Things (IoT). This system aims to increase efficiency in aquarium or fish pond management by integrating various control and monitoring functions in real-time. In this system, the automatic fish feeder uses a programmable dispenser mechanism to provide feed in predetermined amounts and times. Temperature control is carried out using temperature sensors and heating or cooling actuators, to maintain water temperature conditions within the optimal range. In addition, water pH monitoring is carried out through a pH sensor connected to the system to ensure the water quality remains ideal for fish health. Data from these sensors is sent in real-time to the IoT platform, enabling remote monitoring and control via webbased or mobile applications. The results of implementing this system show increased efficiency in feeding, increasing operational efficiency, reducing human error, and providing quality fish, as well as maintaining more stable and optimal environmental conditions. The implementation of this system shows great potential in modern aquaculture applications by utilizing IoT technology for better and responsive management.